HUBUNGAN PENGETAHUAN LINGKUNGAN DENGAN SIKAP PEDULI LINGKUNGAN PADA MAHASISWA PRODI PENDIDIKAN IPS - Anisa Noverita; Haryati; Eka Darliana; Aisah; Try Santi Kisria Darsih; Airil Ramdani (LPPM STKIP AL MAKSUM, 2025)
Current environmental problems, both global and national, are largely caused by human behavior, therefore environmental problems can be minimized by instilling a sense of environmental care. The purpose of this study was to determine the relationship between environmental knowledge and environmental care attitudes. The population and sample in this study were 77 students of the Social Studies Education Study Program at STKIP Al Maksum, class of 2022 and 2023. The instruments used were environmental knowledge test questions and an environmental care attitude questionnaire. Based on the results of the study, the results obtained on the variable of environmental knowledge level of students of the Social Studies Education Study Program at STKIP Al Maksum were included in the High category as many as 46 (60%) respondents, then 31 (40%) respondents were included in the medium category and no respondents were included in the low category. On the environmental care attitude variable, students of the Social Studies Education Study Program were included in the high category as many as 49 (64%) respondents, then 28 (36%) respondents were included in the good category and no respondents were included in the bad category. The results of the study indicate that the closeness of the relationship between knowledge and environmental care attitudes is in the very high category with a correlation coefficient value of 0.985. In addition, a significance value of 0.000 is obtained which is smaller than 0.05 (0.000 < 0.05) so H0 is rejected and Ha is accepted, which means there is a significant and positive relationship between environmental knowledge and the formation of environmental care attitudes of students in the Social Studies Education Study Program.